2022
DOI: 10.1136/bmjgh-2021-007592
|View full text |Cite
|
Sign up to set email alerts
|

Pooled testing of sputum with Xpert MTB/RIF and Xpert Ultra during tuberculosis active case finding campaigns in Lao People’s Democratic Republic

Abstract: IntroductionActive case finding (ACF) of individuals with tuberculosis (TB) is a key intervention to find the 30% of people missed every year. However, ACF requires screening large numbers of individuals who have a low probability of positive results, typically <5%, which makes using the recommended molecular tests expensive.MethodsWe conducted two ACF surveys (in 2020 and 2021) in high TB burden areas of Lao PDR. Participants were screened for TB symptoms and received a chest X-ray. Sputum samples of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…For the in silico analysis, we used the cycle threshold shift determined from Passing-Bablok regression; using either the difference in median cycle threshold values between pooled and individual tests or the bias from the Bland–Altman analysis would lead to similar estimates of the positive percent agreement. The positive percent agreement estimated using this approach was also similar to that reported in studies where all specimens were tested both individually and in pools on the Xpert or Ultra assays 36 , 37 , 39 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For the in silico analysis, we used the cycle threshold shift determined from Passing-Bablok regression; using either the difference in median cycle threshold values between pooled and individual tests or the bias from the Bland–Altman analysis would lead to similar estimates of the positive percent agreement. The positive percent agreement estimated using this approach was also similar to that reported in studies where all specimens were tested both individually and in pools on the Xpert or Ultra assays 36 , 37 , 39 .…”
Section: Discussionsupporting
confidence: 81%
“…type="uri"> https://www.chrisbilder.com/shiny/). 43 Previous studies have reported that pooled testing using the Xpert and Ultra assays would have enabled similarly high proportions of cartridge savings 36 , 37 , 39 . During testing, 4.6% of assays run had an invalid result, similar to what has been reported elsewhere for these assays, 28 which contributed to decreased testing efficiency as compared to the theoretical efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] The difference between the total actual number of individual tests performed and the theoretical number of tests per person when employing the pooling strategy represented the number of tests saved. For the primary analysis, we assumed pool size of four based on prior studies and that both individual and pooled testing were 100% sensitive and speci c. [32,33] We then modeled four ordinal screening and testing approaches with increasing complexity to estimate incremental savings compared to the previous approach (Fig. 1):…”
Section: Model Structurementioning
confidence: 99%
“…Subsequently, pooled testing has been used successfully to screen large populations for infectious diseases. Pooled testing has been utilized in the laboratory testing of HIV, tuberculosis, hepatitis B and C, as well as the screening of blood donations to the American Red Cross [7][8][9]. Its utility has been demonstrated as a way to analyze large numbers of samples with greater efficiency than individual testing allows.…”
Section: Introductionmentioning
confidence: 99%